The Gnostic Significance of the Qur’anic Word: A Study in the Tafsir "Mawahib al-Rahman" by Imam al-Sabzawari - AlJayashi, Talib; AlArnaouti, Iyad (Al-Adab Journal, 2025)
*AleIrfan*: It is a mental science that emerges from cognitive theory and is linked to the brain, mind, and mental processes. It is a science that considers language from a mental perspective. Language, according to those with a mystical orientation, is not seen as an independent entity to be studied in isolation but is connected to mental and perceptual processes. Consequently, the meaning of a Quranic term can be viewed from a perspective different from the linguistic context, resulting from the mind and intellect and related to intention and context. Some interpreters have used the science of cognition in interpreting the Quran, referred to as symbolic interpretation. This involves interpreting the Quran not by its apparent meaning but through hidden indications perceived by mystics and Sufis. These interpreters believe that texts have apparent meanings but also contain subtle indications revealed to those on a mystical path. This type of interpretation differs from that of esoteric sects. The mystical method does not deny the apparent meaning but encourages it, asserting that it must be understood first. In contrast, esoteric sects disregard the apparent meaning entirely, focusing solely on the hidden meaning.